Editorial [Hot Topic: HIV-1 Reverse Transcriptase Inhibitors: Drug Resistance and Drug Development (Executive Editors: Nicolas Sluis-Cremer and Ted Ross)] - Sluis-Cremer, Nicolas; Ross, Ted (Current Pharmaceutical Design, 2006)
HIV-1 reverse transcriptase (RT) is a multifunctional enzyme that facilitates the conversion of the viral singlestranded (+) RNA genome into double-stranded DNA. The enzyme exhibits both a DNA polymerase activity, that can use either RNA or DNA as a template, and a ribonuclease H (RNase H) activity that specifically degrades the RNA strand of RNA:DNA duplexes. Due to its essential role in the HIV life-cycle, RT is a primary target for anti- HIV drug development. To date, the United States Food and Drug Administration has approved 11 RT inhibitors (RTIs) for clinical use. These can be classified into two distinct therapeutic groups: (i) nucleoside and nucleotide RT inhibitors (NRTI) which include zidovudine (AZT), stavudine (d4T), didanosine (ddI), zalcitabine (ddC), lamivudine (3TC), emtricitabine (FTC), abacavir (ABC) and tenofovir disoproxil fumarate (PMPA); and (ii) the nonnucleoside RT inhibitors (NNRTI) which include nevirapine, delavirdine and efavirenz. The emergence of HIV-1 viral resistance to the available RTIs has limited their efficacy for long-term clinical use and has necessitated the development of new inhibitors that are active against both wild-type and resistant strains of the virus. In this directed issue of Current Pharmaceutical Design, we solicited review articles from leaders in the field who shed new paradigms into RTI drug resistance and strategies for developing new therapeutics against HIV- 1 RT. In general the review articles can be broadly categorized into three categories: (i) those that deal with resistance; (ii) those that deal with designing better inhibitors against existing drug targets; and (iii) those that identify novel drug targets in HIV-1 RT. The mechanism(s) of resistance of HIV-1 to RTIs has been the focus of many excellent review articles. The 3 review articles in this issue, contributed by Drs Luis Menéndez-Arias (Spain), Walter Scott (USA) and Marilyn Kroeger Smith (USA), do not re-capitulate past articles, but focus on previously under-explored areas of drug resistance. In this regard, Menéndez-Arias et al. examine the role of amino acid insertions and deletions in HIV-1 RTI multi-drug resistance and viral replication fitness [1]. Smith and Scott discuss the influence of natural substrates and inhibitors in the infected cell on the nucleotide excision mechanism of HIV-1 resistance to NRTIs [2]. Kroeger Smith et al. highlight the contribution that computational chemistry can make toward understanding HIV-1 resistance and drug development [3]. NNRTIs are allosteric inhibitors that bind to a non-active site pocket in HIV-1 RT, termed the NNRTI-binding pocket (NNRTI-BP). One major limitation of this class of inhibitors is that single mutations in the NNRTI-BP often yield cross-resistance to all NNRTI. In this issue, Dr Karen Anderson (USA) has contributed an article that provides succinct insights into the kinetic mechanisms of action of, and resistance to, NNRTI and describes the recent advances that have been made to create NNRTI which are more potent and less susceptible to existing drug resistance mutations [4]. The identification of novel drug targets and/or the development of new classes of antiviral compounds are essential in the fight against HIV/AIDS. The 11 existing FDA-approved RTIs all target the DNA polymerase activity of the enzyme, however there are other targets in HIV-1 RT that can be exploited to develop new therapeutic classes of RTIs. These include translocation, dimerization and RNase H activity. Translocation describes the movement of polymerases along the nucleic acid template after each nucleotide addition reaction. Translocation is often viewed as a kinetically